2013
DOI: 10.1074/jbc.m112.446633
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines Induce NOTCH Signaling in Nucleus Pulposus Cells

Abstract: Background:The regulation of NOTCH signaling under inflammatory conditions in the nucleus pulposus is unknown. Results: Expression of select NOTCH pathway genes, including NOTCH2 and NOTCH signaling, is regulated by IL-1␤ and TNF-␣. Conclusion: Inflammatory cytokines promote NOTCH signaling in disc. Significance: NOTCH signaling may play a role in pathogenesis of disc disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 43 publications
3
86
0
Order By: Relevance
“…Also, MMP-10 expression (at mRNA and protein levels) was increased in the symptomatic degenerate IVD, when compared to non-symptomatic one-possibly contributing to matrix degradation and initiation of nociception [71]. An additional perspective is given by studies that identified factors not naturally produced by native IVD cells: immunoreactivity for IL-4, IL-6, IL-12 and interferon (IFN)-g was modest in surgical IVD tissue, being higher in herniated IVD samples and virtually non-existent in the control NF-kB and MAPK!NOTCH pathway protrusion NP cells [109] rsif.royalsocietypublishing.org J. R. Soc. Interface 12: 20141191 samples taken from post-mortem non-degenerated IVDs [122].…”
Section: Post-mortem Samplesmentioning
confidence: 99%
“…Also, MMP-10 expression (at mRNA and protein levels) was increased in the symptomatic degenerate IVD, when compared to non-symptomatic one-possibly contributing to matrix degradation and initiation of nociception [71]. An additional perspective is given by studies that identified factors not naturally produced by native IVD cells: immunoreactivity for IL-4, IL-6, IL-12 and interferon (IFN)-g was modest in surgical IVD tissue, being higher in herniated IVD samples and virtually non-existent in the control NF-kB and MAPK!NOTCH pathway protrusion NP cells [109] rsif.royalsocietypublishing.org J. R. Soc. Interface 12: 20141191 samples taken from post-mortem non-degenerated IVDs [122].…”
Section: Post-mortem Samplesmentioning
confidence: 99%
“…A Notch signalling inhibitor, L685458, blocked hypoxic induction of the activity of the Notch-responsive luciferase reporters 12xCSL and CBF1 and reduced AF cell proliferation. In a more recent study, an increase of selective Notch receptors (Notch-1 and -2), ligand (JAGGED2), and target genes (HES1, HEY1, and HEY2) was observed in NP cells following treatment with TNF-α or IL-1β [182]. Taking into account the fact that expression of Notch-2 and IL-1β was significantly increased in histologically degenerate discs compared with non-degenerate discs, Notch signalling may play an important role in pro-inflammatory cytokine mediated degenerative processes of the IVD.…”
Section: Notch Pathwaymentioning
confidence: 96%
“…Activation of the Notch signaling pathway has been reported to promote IVD cell proliferation [132]. A study from Wang et al [133] showed that TNF-α up-regulates the expression of Notch1 and Notch2 receptors along with their ligand Jagged-2, and target genes HES1, HEY1, and HEY2 in rat NP cells. They also found that the levels of Notch2 are higher in degenerative human IVD tissues than those in nondegenerative IVD tissues [133].…”
Section: Tnf-α Stimulates the Proliferation Of Np Cellsmentioning
confidence: 99%
“…A study from Wang et al [133] showed that TNF-α up-regulates the expression of Notch1 and Notch2 receptors along with their ligand Jagged-2, and target genes HES1, HEY1, and HEY2 in rat NP cells. They also found that the levels of Notch2 are higher in degenerative human IVD tissues than those in nondegenerative IVD tissues [133]. Thus, in addition to the NF-κB, JNK, and p38 MAPK pathways, TNF-α may also promote NP cell proliferation through the Notch signaling.…”
Section: Tnf-α Stimulates the Proliferation Of Np Cellsmentioning
confidence: 99%